Anthropologists on Home Turf: How Green Is the Grass? - Lithman, Yngve Georg (Anthropologica, 2022)
When embarking upon studies of "our own" societies, anthropologists face strong competition from other disciplines. However, the value of the anthropological contribution to the study of sport will derive from cultivating traditional anthropological strengths. Methodologically, the anthropological tool box will need some re-tooling The anthropological "grass-root" perspective is important, also as a distinguishing disciplinary feature, as will be attention to ritual, bodies and embodiment, and aesthetics. Hereby anthropologists can get at the cultural meaning-creation in sports, and why and how sport is a significant social phenomenon. The anthropological study of sports has a clear potential to let small matters speak loudly to large issues in our societies